Changes of Groundwater Quality in the Sorrounding Pollution Sources Due to Earthquake Dissaster - Sudarmadji Sudarmadji (Universitas Muhammadiyah Surakarta, 2006)
Groundwater is the main domestic water supply of the population of the Yogyakarta Special Region, both in the urban and as well as in the rural area due to its quantity and quality advantages. The rapid population growth has caused an increase of groundwater demand, consequently it is facing some problems to the sustainability of groundwater supply. Lowering of groundwater level has been observed in some places, as well as the degradation of groundwater quality. Earthquake which stroke Yogyakarta on 27 May 2006, damaged buildings and other infrastructures in the area, including roads and bridges. It might also damage the underground structures such as septic tanks, and pipes underneath the earth surface. It might cause cracking of the geologic structures. Furthermore, the damage of underneath infrastructures might create groundwater quality changes in the area. Some complains of local community on lowering and increasing groundwater level and groundwater quality changes were noted. Field observation and investigation were conducted, including collection of groundwater samples close to (the) pollution sources. Laboratory analyses indicated that some parameters increased to exceed the drinking water quality standards. The high content of Coli form bacteria possibly was caused by contamination of nearby septic tanks or other pollution sources to the observed groundwater in the dug well.